Complex formation of Cm(III) with formate studied by time-resolved laser fluorescence spectroscopy - Fröhlich, Daniel R.; Skerencak-Frech, Andrej; Panak, Petra (Applied geochemistry, 2015)
Pore waters of natural clays, which are investigated as potential host rock formations for high-level nuclear waste, are known to contain large amounts of low-molecular weight organic compounds. These small organic ligands might impact the aqueous geochemistry of the stored radionuclides and, thus, their migration behavior. In the present work, the complexation of Cm(III) with formate in aqueous NaCl solution is investigated by time-resolved laser fluorescence spectroscopy (TRLFS) as a function of the ionic strength (0.5-3.0mol/kg), the ligand concentration (0-0.2mol/kg) and the temperature (20-90°C). The Cm(III) speciation is determined by deconvolution of the emission spectra. The obtained distribution of Cm(III) species is used to calculate the conditional stability constants (logK′(T)) at a given temperature and ionic strength which are extrapolated to zero ionic strength by using the specific ion interaction theory (SIT). Thus, the thermodynamic logK0n(T) values for the formation of [Cm(Form)n](3−n)+ (n=1, 2) and the ion interaction coefficients (ε(i,k)) for [Cm(Form)n](3−n)+ (n=1, 2) with Cl− are obtained. The logK01(T) (2.11 (20°C)-2.49 (90°C)) and logK02(T) values (1.17 (30°C-2.01 (90°C)) increase continuously with increasing temperature. The logK0n(T) values are used to derive the standard reaction enthalpies and entropies (ΔrH0m, ΔrS0m) of the respective complexation reactions according to the Van’t Hoff equation. In all cases, positive ΔrH0m and ΔrS0m values are obtained. Thus, both complexation steps are endothermic and entropy-driven.